The One and Only: Single-Bidding in Public Procurement - Vitezslav Titl (CESifo GmbH, 2025)
Approximately 42% of European public procurement contracts are awarded to a sole bidder. As this market represents about one-seventh of GDP in developed countries, any inefficiency is a first-order concern. This paper examines a Czech reform that prohibited awarding such single-bid contracts. Using a difference-in-differences approach, I find the reform reduced prices by 6.1% relative to estimated costs, with no evidence of quality reduction. Furthermore, I provide suggestive evidence that procuring authorities try to actively get more bidders and that the prices of procurement contracts supplied by politically connected and anonymously owned firms were not reduced after the reform.
Keywords: D44; D72; H57; 330; single-bidding; public procurement; political connections; corruption